El Inca Garcilaso de la Vega: La “Ley natural” frente a las “Leyes nuevas” - Serna Arnaiz, Mercedes (Mercurio Peruano, 2019)
Valladolid debate (1550-1551) faced two conflicting views on the attitude that the Spanish crown should keep to Native Americans, represented by Juan Gines de Sepulveda and Bartolome de Las Casas. The ideas of the latter decisively influenced the drafting of the so-called New Laws of the Indies, but found a widespread rejection in America by different sectors of the colonial power. The opposition to the ideas of Las Casas present in Inca Garcilaso de la Vega’s General History of Peru (second part of his Royal Commentaries) would be based on the Jesuit background of the work. This opposed to the theses of the Dominican Order political pragmatism and religious and cultural syncretism project.